Multiple Functions for the Basic Amino Acids of the Human T-Cell Leukemia Virus Type 1 Matrix Protein in Viral Transmission - Le Blanc, Isabelle (American Society for Microbiology, 1999)
We studied the involvement of the human T-cell leukemia virus type 1 (HTLV-1) Gag matrix protein in the cell-to-cell transmission of the virus using missense mutations of the basic amino acids. These basic amino acids are clustered at the N terminus of the protein in other retroviruses and are responsible for targeting the Gag proteins to the plasma membrane. In the HTLV–bovine leukemia virus genus of retroviruses, the basic amino acids are distributed throughout the matrix protein sequence. The HTLV-1 matrix protein contains 11 such residues. A wild-type phenotype was obtained only for mutant viruses with mutations at one of two positions in the matrix protein. The phenotypes of the other nine mutant viruses showed that the basic amino acids are involved at various steps of the replication cycle, including some after membrane targeting. Most of these nine mutations allowed normal synthesis, transport, and cleavage of the Gag precursor, but particle release was greatly affected for seven of them. In addition, four mutated proteins with correct particle release and envelope glycoprotein incorporation did not however permit cell-to-cell transmission of HTLV-1. Thus, particle release, although required, is not sufficient for the cell-to-cell transmission of HTLV-1, and the basic residues of the matrix protein are involved in steps that occur after viral particle release.